Sosialisasi Tertib Berlalu Lintas bagi Siswa SMP di Lagosi: Membangun Kesadaran dan Keselamatan di Jalan Raya - Ismail Ali; Yustiana; Sabariah; Risnayanti; Baso Hamarullah Halim; Muh. Rizki; Muh. Dia Ikhsan Perdana (YP-SDI Lamaddukelleng, 2024)
The issue of traffic safety represents a significant concern in a number of contexts, including among students. The objective of the traffic order socialisation programme is to enhance the awareness and knowledge of junior high school students in Lagosi regarding the significance of orderly behaviour on the road. The socialisation programme comprised a series of activities, including the presentation of materials on traffic signs, basic traffic rules, and the adverse consequences of violating traffic regulations. Furthermore, simulations and interactive discussions were conducted with the objective of reinforcing students' comprehension of the scenarios they frequently encounter on a daily basis while traversing the roadways. It is anticipated that this pedagogical strategy will facilitate not only an understanding of traffic regulations, but also their practical application in the students' daily lives, whether as pedestrians, cyclists, or passengers. The results of this activity demonstrated a notable enhancement in students' comprehension of the significance of road safety, accompanied by a more favourable shift in attitude towards the practice of orderly traffic conduct. It is therefore anticipated that this socialisation programme will serve as an initial step in the moulding of a younger generation that is more disciplined and aware of traffic safety.